Rheological properties of gelatin, carrageenan and locust bean gum mixtures - Jones, Guy Matthew John (2004)
This thesis reports data on blends of carrageenan (0.3%w/w) and locust bean gum (0.3%w/w) in the presence of biopolymers, particularly gelatin of varying concentration. Particular attention is given to their behaviour on autoclaving since this is relevant to one of the most important applications of these materials as gelling agents in canned meat products.